PERCEPTIONS AND OPINIONS ON THE BIOETHICS OF EUTHANASIA IN A BRAZILIAN POPULATION SAMPLE (REMUNOM, 2023)
Euthanasia is a complex and controversial issue that involves crucial decisions related to life and death, respecting the autonomy and dignity of individuals. The main objective of this study was to investigate the position of a population sample on the bioethics of euthanasia, taking into account social, cultural and moral aspects. To achieve this goal, descriptive quantitative research was conducted using an online questionnaire as a data collection instrument. The sample was obtained by snowball sampling, with participants living in Brazil. Participants were asked about their knowledge of euthanasia, their opinion on the subject, and related concepts such as orthothanasia and assisted suicide. In addition, demographic information, such as age, religion and education level, was collected to identify possible relationships between these aspects and the position regarding euthanasia. Preliminary results showed that most participants were knowledgeable about the term euthanasia, but not all could explain the concept accurately. In addition, there was a diversity of opinions regarding the practice of euthanasia, with a significant portion of the participants being in favor. However, it was also noted that many participants did not know the terms orthothanasia and assisted suicide. Statistical analysis of the data revealed some associations between the position regarding euthanasia and demographic characteristics, such as age and religion. For example, younger participants seemed to have a clearer understanding of the concept and were more likely to be supportive of the practice. In addition, religious beliefs also influenced the positioning of participants, with Christians being more likely to be opposed to euthanasia. In conclusion, this study demonstrated that the position regarding euthanasia is influenced by several factors, including knowledge on the subject, demographic characteristics and religious beliefs. Conducting research in this area is fundamental to understand the perspectives and values of society in relation to euthanasia, contributing to the ethical debate and the formulation of public policies related to the subject.